ISSUES IN LANGUAGE AND IDENTITY RESEARCH IN APPLIED LINGUISTICS - Block, David (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Identity has become a key construct in applied linguistics over the past 30 years, as more and more researchers have heeded Norton Peirce’s (1995: 12) call for ‘a comprehensive theory of social identity that integrates the language learner and the language learning context’. In this article, my aim is to discuss what I see as issues arising in identity research in applied linguistics. I start with a brief consideration of why identity has become so central in applied linguistics, before discussing the poststructuralist model of identity which has been adopted by the vast majority of researchers. I then move to consider three more substantive issues: (1) the potential benefits of a more psychological angle when most language and identity research tends to be predominantly social; (2) the importance of clarifying the interrelationship between individual agency and social structures in language and identity research; and (3) the potential benefits of including a socioeconomic stratification and social class angle in research which tends to prime identity politics (identity inscriptions such as race, ethnicity, gender, sexuality, nationality and language), over the material conditions of life. Resumen La identidad se ha convertido en un constructo clave en la lingüística aplicada durante los últimos 30 años, dado que cada vez más investigadores han seguido la llamada de Norton Peirce (1995: 12) en lo que se refiere a ‘a comprehensive theory of social identity that integrates the language learner and the language learning context’. En este artículo, mi intención es tratar lo que considero como cuestiones claves en las investigaciones sobre la “identidad” en la lingüística aplicada. Empiezo con una breve reflexión sobre por qué la identidad ha llegado a ser tan importante en la lingüística aplicada, para pasar después a examinar el modelo posestructuralista de la identidad que han adoptado la gran mayoría de los investigadores. En segundo lugar paso a considerar tres cuestiones: (1) los beneficios potenciales de una perspectiva más psicológica en este tipo de investigaciones ya que la mayoría de ellas sobre la lingüística y la identidad tienden a considerar fundamentalmente el aspecto social; (2) lo importante que es clarificar la interrelación entre la agencia individual y la estructura social en las investigaciones sobre lingüística e identidad; y (3) los beneficios potenciales de incorporar la estratificación socio-económica y clase social en investigaciones que tienden a dar prioridad a las políticas identitarias (inscripciones de la identidad como la raza, la etnia, el género, la sexualidad, la nacionalidad y la lengua) sobre las condiciones materiales de la vida.